Ge-on-insulator lateral p-i-n waveguide photodetectors for optical communication - Cheng, Chin-Yuan (2020)
We report high-performance lateral p-i-n Ge waveguide photodetectors (WGPDs) on a Ge-on-insulator (GOI) platform that could be integrated with electronic-photonic integrated circuits (EPICs) for communication applications. The high quality Ge layer affords a low absolute dark current. A tensile strain of 0.144% in the Ge active layers narrows the direct bandgap to enable efficient photodetection over the entire range of C- and L bands. The low-index insulator layer enhances optical confinement, resulting in a good optical responsivity. These results demonstrate the feasibility of planar Ge WGPDs for monolithic GOI-based EPICs.